How to Build Cash Management Capacity in Fragile States and Low-Income Developing Countries - Pattanayak, Sailendra (IMF How To Notes; How-To Note ;, 2022)
Fiscal institutional capacity in most fragile states (FS) and several low-income developing countries (LIDCs) is much lower than in other countries. Governments in these countries face several cash management challenges because they often lack credible budgets, have smaller and less diversified revenue bases, have limited access to financial markets, and rely largely on donors to fund a large portion of their budgets. Available public funds in these countries often remain dispersed outside the control of the ministry of finance. In the absence of a good cash forecasting function, these countries typically resort to cash rationing to meet their priority spending needs, often in an ad hoc manner, which can adversely affect budget execution and achievement of fiscal policy targets. This note sets out the key objectives and building blocks of a cash management function in FS and LIDCs. It suggests several measures to progressively build cash management capacity in three interrelated areas: consolidating cash resources, forecasting cash flows, and managing cash balances with sound institutional setups.